Decreased Hip Labral Width Measured via Preoperative MRI is Associated with Inferior Outcomes for Arthroscopic Labral Repair. Issue 7 (31st July 2020) - Baron, Samuel; Samim, Mohammed; Burke, Christopher; Meislin, Robert; Kaplan, Thomas Youm, Daniel
Objectives: There are few pre-operative prognostic factors for hip labral repair outcomes. The objective of this study was to determine if hip labrum width measured on MRI was predictive of outcomes Methods: A retrospective review of prospectively gathered hip arthroscopy patients from 2010 to 2017 was performed. Inclusion criteria was defined as: patients >18 years old with radiographic evidence of femoroacetabular impingement who underwent a primary labral repair with >2 years of follow-up. Exclusion criteria was defined as: inadequate imaging, prior hip surgery, Tonnis grade ≥2 or lateral central edge angle <25 degrees. An a-priori power analysis was performed. MRI measurements of labral width were conducted by two blinded musculoskeletal fellowship-trained radiologists at standardized "clockface" locations using a previously validated technique. Outcomes were assessed using the Harris Hip Score (HHS), Modified HHS (mHSS), and NonArthritic Hip Score (NAHS). For mHHS, a minimal clinically important difference (MCID) and Patient Acceptable Symptomatic State (PASS) of 8 and 74 were used, respectively. Patients were divided into groups by labral width of ≤4mm and >4mm. Statistical analysis was performed using: linear and polynomial regression, Mann-Whitney U, Fischer exact, and interclass-correlation coefficients (ICC) testing Results: One hundred and three patients (107 hips) met criteria (mean age 39.4years+/-17, BMI 25.0+/-4, 51%right-sided, 68%female). Mean labrum measurements and number of patients with ≤4mm labrums at the 12:00 (indirect rectus), 3:00 (Psoas U), and 1:30 (point ½ between) positions were 7.1mm+/-2.2; 15 labrums≤4mm, 7.0 mm+/-2.0;13 labrums≤4mm, and 5.5+/-1.9; 27 labrums≤4mm, respectively. ICC agreements were good to excellent between readers at all positions (0.83-0.91, p<0.001). Pre-operative HHS, mHHS, and NAHS were not statistically different (p>0.05). Sex, laterality, and BMI had no significant effect on outcomes (p>0.05).HHS, mHHS, and NAHS scores were found to be significantly lower in the ≤4mm group at each location tested (p<0.001); including mHHS at the 12:00 (67vs87), 3:00, (69vs87) and 1:30 (74vs88) positions. The proportion of ≤4mm patients that reached MCID was significantly lower(p<0.001) at the 12:00 (47%vs91%), 3:00 (54%vs89%) and 1:30 (63%vs93%) positions. The proportion of ≤4mm patients above PASS was significantly lower (p<0.001) at the 12:00 (40%vs84%), 3:00 (31%vs84%) and 1:30 (52%vs86%) positions.Linear regression modelling was not significant at any position (p>0.05). Polynomial regression was significant at the 12:00 (R2=0.23, p<0.001), 3:00 (R2=0.17, p<0.001), and 1:30 (R2=0.26, p<0.001). Conclusion: A non-linear relationship may exist between labral width and patient outcomes following labral repair. Labrum width of ≤4mm measured via MRI may negatively impact labral repair outcomes. Future research may determine if torn labrums ≤4mm should be reconstructed instead of repaired.